2004
DOI: 10.1007/s00467-004-1426-z
|View full text |Cite
|
Sign up to set email alerts
|

Generalized atherosclerosis sparing the transplanted kidney in Schimke disease

Abstract: Schimke-immuno-osseous dysplasia (SIOD) is a multisystem disorder caused by a mutation of the chromatin remodeling protein. The main clinical findings are spondyloepiphyseal dysplasia with disproportional growth deficiency, nephrotic syndrome with focal and segmental glomerulosclerosis, and defective cellular immunity. Transitory ischemic attacks due to vaso-occlusive processes are still an untreatable and life-limiting complication in patients with SIOD. The underlying pathophysiology of vaso-occlusive proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 21 publications
4
40
0
5
Order By: Relevance
“…Glomerular disease did not recur in the renal allograft of SD600 or SD840, supporting a cell-autonomous mechanism. Also, Lücke et al 24 recently showed that atherosclerosis did not recur within the renal allograft during 18 years after transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Glomerular disease did not recur in the renal allograft of SD600 or SD840, supporting a cell-autonomous mechanism. Also, Lücke et al 24 recently showed that atherosclerosis did not recur within the renal allograft during 18 years after transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to these earlier generalizations, we recently presented a patient with all the symptoms of severe SIOD who reached the age of 23 years [Lü cke et al, 2004]. In addition, Lou et al [2002], published a 20-year-old woman with the molecular and clinical criteria for the severe form of SIOD.…”
Section: Molecular Biology Findingsmentioning
confidence: 91%
“…Our patient had all her ischemic attacks in August and September, but she had no heath intolerance. It has been reported that diffuse and progressive atherosclerosis is the basic cause of cerebrovascular events in patients with Schimke immuno-osseous dysplasia (7,10). Although hypertension, hyperlipidemia, proteinuria and ESRD which were also found in our patient are significant risk factors for atherosclerosis, symptoms of cerebrovascular ischemia have been observed in patients with SIOD even before renal disease started (13).…”
Section: To the Editormentioning
confidence: 59%
“…High blood pressure in our patient was controlled with enalapril and amlodipine. Interestingly, it was reported that glomerulosclerosis did not recur after renal transplantation in this patient (9,10).…”
Section: To the Editormentioning
confidence: 99%